Lokale opfattelser af diarré i Baluchistan - Samuelsen, Helle (Tidsskriftet Antropologi, 2019)
Diarrhoea is one the most common diseases among children in rural Baluchistan and contributes to a very high child mortality rate. A study in which 60 mothers were interviewed shows that humoral theories of hot and cold food play a prominent role in local people’s beliefs about causes of childhood diarrhoea. However, data on management of diarrhoea show that the humoral balance is not redressed by intake of cold food. Instead parhaiz, a limited diet, is used as treatment. Also biomedical anti-diarrhoeal drugs are becoming popular. Oral Rehydration Therapy (ORT) has a very limited popularity because the qualities ascribed to it by the local population do not fit into a humoral perception of treatment. This study from Baluchistan and other similar studies belong to a medical anthropological tradition where specific biomedical symptoms or diseases are studied. It is suggested that our understanding of how humoral theories are applied today would benefit if analysed in a wider anthropological context.